Gossypetin targets the liver-brain axis to alleviate pre-existing liver fibrosis and hippocampal neuroinflammation in mice - Xu, Cenlu; Tai, Haoran; Chu, Yanan; Liu, Ye; He, Jiacheng; Wang, Yiran; Su, Bingyin; Li, Shurong (Frontiers in Pharmacology, 2024)
Liver fibrosis occurs in response to chronic damage and inflammation to the liver. Leaving untreated, it can lead to decreased liver function and can eventually progress to cirrhosis, a more advanced and irreversible state of liver damage. Clinical investigations showed that chronic liver disease associated with neurological symptoms including anxiety, depression, and cognitive decline. However, few therapeutic options are available for treating liver and related brain pathologies simultaneously. In this study, we aim to find therapeutic candidates that target the liver-brain axis. Gossypetin, a flavonoid from sedum, shows promising capability in treating liver and brain pathologies in CCl4-induced mouse model. Short term of gossypetin administration is sufficient to ameliorate impaired liver function and pre-existing liver fibrosis, suppress MKK3/6-p38 MAPK and p53 activation, and abolish the activation of hepatic stellate cells and Kupffer cells. Although we observe no neuronal loss in the brain of mice with liver fibrosis, we do observe astrogliosis and microglial activation in certain brain regions, especially the hippocampus. Brief gossypetin administration also shows potential in alleviating neuroinflammation in these regions. These results suggest that gossypetin can target the liver-brain axis and be a promising candidate for treating chronic liver fibrosis patients with neurological symptoms.